Basal forebrain mediated increase in brain CRF is associated with increased cholinergic tone and depression. (30th June 2017) - Gollan, Jackie K.; Dong, Hongxin; Bruno, Davide; Nierenberg, Jay; Nobrega, José N.; Grothe, Michel J.; Pollock, Bruce G.; Marmar, Charles R.; Teipel, Stefan; Csernansky, John G.; Pomara, Nunzio
Highlights: Major depression is a devastating disease that generates significant suffering and cost. CSF CRF and MDD interaction predicted basal forebrain cholinergic nuclei volume. These results contribute to our understanding of the role of brain's stress axis in depression.